Phenylpropanoids from maize pericarp: resistance factors to kernel infection and fumonisin accumulation by Fusarium verticillioides - Sampietro, Diego Alejandro (2013)
The aim of this work was to investigate the role of pericarp phenylpropanoids as resistance factors to F. verticillioides in eleven maize genotypes. Disease severity and kernel fumonisin accumulation were measured after inoculation with F. verticillioides and related to contents of pericarp phenylpropanoids in field trials conducted during 2 years. Grain fumonisin concentrations were highly dependant on disease severity of the genotypes (r = 0.88). A detailed analysis of pericarp phenylpropanoids indicated the presence of trans-ferulic acid (tFA), cis-ferulic acid (cFA), p-coumaric acid (pCA), and five diferulates (DFAs). The most prominent diferulates were 8,5′-diferulic acid benzofuram form (8,5′-DFAbz), followed by 8,5′-DFA and 8,8′-DFA. Except for cFA, the most resistant genotypes exhibited high levels of phenylpropanoids which were related to low levels of disease severity and grain fumonisin concentration (−0.61 > r > −0.90). A stepwise regression analysis revealed that total diferulates was the best explanatory parameter for variability of disease severity (r 2 = 0.71). Grain fumonisin concentration was well depicted by contents of total diferulates, 8,5′DFAbz and pCA (r 2 = 0.82). Our findings suggest that high level of phenylpropanoids in the kernel pericarp is a trait associated to less disease severity and fumonisin accumulation caused by F. verticillioides. Further research is in progress to map quantitative trait loci for these cell wall components in bi-parental populations derived by crossing resistant and susceptible genotypes included in this study.